2022
DOI: 10.3389/fpls.2021.791256
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield Preharvest Prediction Based on Bean Pods and Leaves Image Recognition Using Deep Learning Neural Network Combined With GRNN

Abstract: Soybean yield is a highly complex trait determined by multiple factors such as genotype, environment, and their interactions. The earlier the prediction during the growing season the better. Accurate soybean yield prediction is important for germplasm innovation and planting environment factor improvement. But until now, soybean yield has been determined by weight measurement manually after soybean plant harvest which is time-consuming, has high cost and low precision. This paper proposed a soybean yield in-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In that study, apart from architectural traits, seed coat color was also documented for diversity characterization of germplasm according to UPOV classification. Recently, several pieces of literature reported the variability of seed traits captured using imaging sensors in soybean ( Yuan et al., 2019 ; Baek et al., 2020 ; Yang et al., 2021 ; Lu et al., 2022 ). However, the present work demonstrated the application of imaging sensors to predict SW from SAT, which is an important yield-contributing trait to identify superior donors for breeding better soybean crop plants.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, apart from architectural traits, seed coat color was also documented for diversity characterization of germplasm according to UPOV classification. Recently, several pieces of literature reported the variability of seed traits captured using imaging sensors in soybean ( Yuan et al., 2019 ; Baek et al., 2020 ; Yang et al., 2021 ; Lu et al., 2022 ). However, the present work demonstrated the application of imaging sensors to predict SW from SAT, which is an important yield-contributing trait to identify superior donors for breeding better soybean crop plants.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean is not only one of the five major crops in the world, but also an essential high protein grain and oil crop (Yu et al, 2022). As a leaf homologous organ (Lu et al, 2022), soybean pods are an important factor in determining grain yield and quality. Therefore, it is necessary to detect the pod's quality of soybean plants in different growth stages and analyze the phenotypic characters of different varieties of pods.…”
Section: Introductionmentioning
confidence: 99%
“…Ning et al (2021) proposed a phenotypic information extraction method for the soybean plant based on IM-SSD+ACO algorithm, which realized the extraction of soybean phenotypic traits including the number of pods, plant height, number of branches, main stem and plant type, effectively. Lu et al (2022) proposed a method based on the YOLOv3 algorithm to predict soybean yield according to the number of pods and leaves. Zhang et al (2021) constructed a soybean yield prediction model based on skew parameters using the color of soybean canopy leaves at different growth stages as input values.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different from parametric statistical approaches, they capture the complex characteristics of a dataset in addition to being slightly susceptible to noise and outliers and being suitable for nonlinearly separable problems common to agricultural experimentation ( Kavzoglu and Mather, 2003 ; Sudheer et al, 2003 ; Haykin, 2008 ). Currently, at the experimental level, ANN models have been used in the prediction of genetic values ( Soares et al, 2015 ), adaptability and stability ( do Carmo Oda et al, 2019 ), phenotyping ( Sá, 2018 ), yield estimates ( Lu et al, 2022 ), genetic diversity ( Rahimi et al, 2019 ; Taratuhin et al, 2020 ), disease detection, and classification ( Hang et al, 2019 ; Trivedi et al, 2021 ). Moreover, they have demonstrated that the efficiency in the breeding stages can be increased, which can reduce the time and cost of obtaining high-performance cultivars.…”
Section: Introductionmentioning
confidence: 99%